2019
DOI: 10.1017/wet.2018.111
|View full text |Cite
|
Sign up to set email alerts
|

Horseweed (Conyza canadensis) Suppression from Cover Crop Mixtures and Fall-Applied Residual Herbicides

Abstract: Horseweed is a problematic weed to control, especially in no-tillage production. Increasing cases of herbicide resistance have exacerbated the problem, necessitating alternative control options and an integrated weed management approach. Field experiments were conducted to evaluate horseweed suppression from fall-planted cover crop monocultures and mixtures as well as two fall-applied residual herbicide treatments. Prior to cover crop termination, horseweed density was reduced by 88% to 96% from cover crops. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 35 publications
(46 reference statements)
10
24
0
Order By: Relevance
“…At Isabella 2018, all cover-crop treatments, with exception of WWH, reduced horseweed density 46% to 56% compared with NC (Table 5). Similarly, previous studies have found cover crops reduced horseweed density 80% at the time of termination compared with NC (Wallace et al 2019;Pittman et al 2019). At Isabella 2019, horseweed densities in the planting-green treatments were 66% lower compared with the early termination treatments (Table 5).…”
Section: Horseweed Suppression At Cover-crop Terminationsupporting
confidence: 71%
“…At Isabella 2018, all cover-crop treatments, with exception of WWH, reduced horseweed density 46% to 56% compared with NC (Table 5). Similarly, previous studies have found cover crops reduced horseweed density 80% at the time of termination compared with NC (Wallace et al 2019;Pittman et al 2019). At Isabella 2019, horseweed densities in the planting-green treatments were 66% lower compared with the early termination treatments (Table 5).…”
Section: Horseweed Suppression At Cover-crop Terminationsupporting
confidence: 71%
“…The five cases where the mixture performed significantly better than the monoculture fell in four categories: cover crop productivity, weed suppression, N retention, and crop yield promotion. All five were situations the mixtures were of legumes with non-legumes and were planted at rates exceeding substitutive rates-anywhere from 123 to 210% of the full rates used for the monocultures (Kaye et al, 2019;Pittman, Barney, & Flessner, 2019;Teasdale & Abdul-Baki, 1998) -causing the effect of plant mixing to be confounded by the effects of seeding rate. The elevated performance of the cover crop mixtures in these five cases could be more a result of elevated seeding rate than the actual mixing of different cover crop 3 26 13 12 6 5 16 11 119 Note.…”
Section: Full Comparisonsmentioning
confidence: 99%
“…Fall-sown cover crops provide direct competition with weed species that have overlapping life cycles, and cover crop residue left on the soil surface after termination can indirectly influence the recruitment and growth rates of summer annual weed species (Ryan et al 2011b;Teasdale et al 2005). Recent studies have demonstrated that integrating cover crops can increase suppression of glyphosateresistant weeds, including fall-and spring-emerging horseweed [Conyza canadensis (L.) Cronquist] (Cholette et al 2018;Pittman et al 2019;Wallace et al 2019) and summer annuals Palmer amaranth (Amaranthus palmeri S. Watson) and waterhemp [Amaranthus tuberculatus (Moq.) Sauer] (Loux et al 2017;Montgomery et al 2018;Wiggins et al 2015).…”
Section: Introductionmentioning
confidence: 99%